2021
DOI: 10.1186/s12864-021-08053-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide scans for signatures of selection in Mangalarga Marchador horses using high-throughput SNP genotyping

Abstract: Background The detection of signatures of selection in genomic regions provides insights into the evolutionary process, enabling discoveries regarding complex phenotypic traits. In this research, we focused on identifying genomic regions affected by different selection pressures, mainly highlighting the recent positive selection, as well as understanding the candidate genes and functional pathways associated with the signatures of selection in the Mangalarga Marchador genome. Besides, we seek t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…The longest shared homozygous segment was detected in ECA 7, with a length of around 25 Mbp. Studies have already reported the same findings in ECA 7, and it is probably an important region conserved for most equine breeds (Ablondi et al, 2019; Grilz‐Seger et al, 2019; Santos, Schettini, et al, 2021). Therefore, selection events and genetic drift initially contribute to the formation of long ROHs (Pemberton et al, 2012).…”
Section: Discussionmentioning
confidence: 53%
“…The longest shared homozygous segment was detected in ECA 7, with a length of around 25 Mbp. Studies have already reported the same findings in ECA 7, and it is probably an important region conserved for most equine breeds (Ablondi et al, 2019; Grilz‐Seger et al, 2019; Santos, Schettini, et al, 2021). Therefore, selection events and genetic drift initially contribute to the formation of long ROHs (Pemberton et al, 2012).…”
Section: Discussionmentioning
confidence: 53%
“…Although we have mainly focused attention on the common candidate regions identified by at least two approaches, it is important to reiterate that each method has specific features implying that non‐overlapping regions of selection signatures across different methods should be treated as complementary information to better understand the different patterns of variation in a population (Santos et al, 2021). In this regard, the Rsb approach identified a region on OAR06 with well‐known candidate genes.…”
Section: Discussionmentioning
confidence: 99%
“…Two heterozygous and two missing genotypes were permitted within each segment. The scanning window was set to 50 SNPs (Ceballos et al, 2018; Santos et al, 2021). The detailed settings were as follows: –homozyg –density 60 –gap 1000 –kb 250 –snp 20, –window‐het 2, –window‐missing 2, –window‐snp 50, –window‐threshold 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the DNA regions that are ROH in the majority of the animals in a breed can be regarded as selection signatures (Grilz‐Seger et al, 2019; Peripolli et al, 2017). Because TD analysis and ROH analysis rely on different measures of genetic fixation/variation, the methods are often used in combination to avoid missing DNA regions of interest (de Simoni Gouveia et al, 2014; Rajawat et al, 2022; Santos et al, 2021; Xia et al, 2021).…”
Section: Introductionmentioning
confidence: 99%